2012
DOI: 10.33073/pjm-2012-043
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Bartonella henselae and Bartonella quintana Antibodies in Croatian Patients Presenting with Lymphadenopathy

Abstract: Between 2007 and 2010, a total of 268 Croatian patients with lymphadenopathy were tested for IgM/IgG antibodies to Bartonella (B.) henselae and B. quintana. Samples from 44.4% patients showed positive IgG antibodies: 35.8% to B. henselae, 6.7% to B. quintana and 1.9% to both Bartonella species. There was no difference in seropositivity between males and females (47.4% vs. 41.5%). Seroprevalence was high in all age groups (40.4-60.9%). Patients from urban and rural areas showed a similar seroprevalence rate (44… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 23 publications
2
6
0
1
Order By: Relevance
“…In our study 72% (34/46) of samples to be tested for the presence of B. henselae were sent between September and March, compatible with data from previous studies [5,6,18]. Many authors considered that seasonal changes in animal reproductive behavior or flea seasonality may be an explanation for this seasonal preference [1,6,20].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In our study 72% (34/46) of samples to be tested for the presence of B. henselae were sent between September and March, compatible with data from previous studies [5,6,18]. Many authors considered that seasonal changes in animal reproductive behavior or flea seasonality may be an explanation for this seasonal preference [1,6,20].…”
Section: Discussionsupporting
confidence: 87%
“…In the present study, 59% of the seropositive patients were above the age of 18, while 41% were under the age of 18. Studies conducted by Sun et al [19] and by Vilibic-Cavlek et al [20] showed similar results suggesting that Bartonella infection may occur in various age groups. Besides, we observed no significant difference in the IgM seropositivity between males (47.4%) and females (41.5%), consistent with other published studies [7,18,21].…”
Section: Discussionmentioning
confidence: 63%
“…Human disease associated to infection with Bartonella species as well as seropositivity to Bartonella spp. has been described from some countries in the Balkans [ 66 , 67 ] but yet not from Albania. The prevalence of Bartonella infection in cats in the Balkan region is largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Se reportan casos de B. henselae en niños con adenitis regional en una muestra amplia de casos. La frecuencia de serología positiva hallada fue superior a otros estudios en niños con adenitis sospechosa por B. henselae quienes reportan frecuencias de 40,4 hasta 73,6% (10)(11)(12) , mielitis, absceso paravertebral; compromiso abdominal como granulomas y microabscesos hepatoesplénicos; compromiso ocular como síndrome óculoglandular de Parinaud, neuritis óptica y retinitis; compromiso pulmonar como neumonitis o derrame pleural. También se reportan endocarditis, pericarditis, púrpura trombocitopénica, anemia hemolítica no inmune, y manifestaciones cutáneas como angiomatosis bacilar y sarpullido (18)(19)(20)(21) .…”
Section: Discussionunclassified